Analysis of Time Loss Injury in Korean Professional Baseball Players - Mun-Ku Song; Hyun-Sik Kang (Exercise science (Seoul, Korea), 2024)
PURPOSE This prospective cohort study aimed to investigate the epidemiology of time-loss (TL) injuries in 68 Korean Baseball Organization (KBO) players aged 26.6±5.4 years (31 pitchers and 37 field players). METHODS Injury data collected during the 2021-2022 KBO league seasons were used to calculate the injury rate (IR), IR ratio (IRR), and TL. IR was calculated as follows: (total number of injuries×100)÷(total number of game exposures). IRR was computed as follows: (IR of pitchers)÷(IR of fielders). TL was defined as an injury that resulted in the inability to compete or participate in standard routines. RESULTS A total of 92 TL injuries were recorded from 5,320 athlete-exposures (1.7 per 100 athlete-exposures). Pitchers exhibited a 1.7-fold increase in IR (IRR =1.69, 95% CI=1.05-2.61, p=.018) and a 2.6-fold increase in the rate of severe injuries that resulted in a TL of ≥3 weeks (IRR=2.59, 95% CI=0.93-7.10, p=.045) compared to field players. The trunk/spine (20.6%) among pitchers and thigh/groin (22.4%) among field players were the most frequently injured body parts. Overuse (38.2%) and batted ball contact (38.2%) were the leading causes of injury among pitchers, whereas noncontact (36.2%) and overuse (17.2%) were the leading causes of injury among field players. Pitchers were most likely to be injured while pitching (55.9%) and fielding (38.2%), whereas field players were most likely to be injured while batting (31.0%) and base running (31.0%). CONCLUSIONS The current findings indicate that the characteristics of the injuries of KBO players differ by position, emphasizing the importance of a position-specific injury prevention program.